The Influence of Solid Microneedles on the Transdermal Delivery of Selected Antiepileptic Drugs - Julia Nguyen; Kevin B. Ita; Matthew J. Morra; Inna E. Popova (MDPI AG, 2016)
The aim of this project was to examine the effect of microneedle rollers on the percutaneous penetration of tiagabine hydrochloride and carbamazepine across porcine skin in vitro. Liquid chromatography-mass spectrometric analysis was carried out using an Agilent 1200 Series HPLC system coupled to an Agilent G1969A TOF-MS system. Transdermal flux values of the drugs were determined from the steady-state portion of the cumulative amount versus time curves. Following twelve hours of microneedle roller application, there was a 6.74-fold increase in the percutaneous penetration of tiagabine hydrochloride (86.42 ± 25.66 µg/cm2/h) compared to passive delivery (12.83 ± 6.30 µg/cm2/h). For carbamazepine in 20% ethanol, passive transdermal flux of 7.85 ± 0.60 µg/cm2/h was observed compared to 10.85 ± 0.11 µg/cm2/h after microneedle treatment. Carbamazepine reconstituted in 30% ethanol resulted in only a 1.19-fold increase in drug permeation across porcine skin (36.73 ± 1.83 µg/cm2/h versus 30.74 ± 1.32 µg/cm2/h). Differences in flux values of untreated and microneedle-treated porcine skin using solid microneedles for the transdermal delivery of tiagabine were statistically significant. Although there were 1.38- and 1.19-fold increases in transdermal flux values of carbamazepine when applied as 20% and 30% ethanol solutions across microneedle-treated porcine skin, respectively, the increases were not statistically significant.